2008
DOI: 10.1364/ao.47.000504
|View full text |Cite
|
Sign up to set email alerts
|

Design and characteristics of refractive index sensor based on thinned and microstructure fiber Bragg grating

Abstract: A refractive index sensor based on the thinned and microstructure fiber Bragg grating (ThMs-FBG) was proposed and realized as a chemical sensing. The numerical simulation for the reflectance spectrum of the ThMs-FBG was calculated and the phase shift down-peak could be observed from the reflectance spectrum. Many factors influencing the reflectance spectrum were considered in detail for simulation, including the etched depth, length, and position. The sandwich-solution etching method was utilized to realize th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 35 publications
(22 citation statements)
references
References 25 publications
0
22
0
Order By: Relevance
“…Our previous work [36] have reported that reflectance ratio of the fiber EW sensor with Bragg grating was not changed by a little fluctuation of the surrounding temperature. The reflectance spectrum of Bragg grating kept original profile, and only red shifted or blue shifted with the change of the surrounding temperature, thus, the reflectance ratio of the fiber sensor with Bragg grating was not attenuated.…”
Section: Temperature Effect Of Bragg Grating Evanescent Wave Fiber Sementioning
confidence: 94%
See 1 more Smart Citation
“…Our previous work [36] have reported that reflectance ratio of the fiber EW sensor with Bragg grating was not changed by a little fluctuation of the surrounding temperature. The reflectance spectrum of Bragg grating kept original profile, and only red shifted or blue shifted with the change of the surrounding temperature, thus, the reflectance ratio of the fiber sensor with Bragg grating was not attenuated.…”
Section: Temperature Effect Of Bragg Grating Evanescent Wave Fiber Sementioning
confidence: 94%
“…[36] Light emitted from Amplified Spontaneous Emission (ASE) routed the circulator to arrive at Bragg grating. The reflected light from the Bragg grating was split into two paths using the coupler (50:50) and interrogated by DWDM and Power meter to obtain Bragg wavelength shift and reflected optical power attenuation.…”
Section: Near-field Nanofluid Concentration Measurementmentioning
confidence: 99%
“…These conditions mean that the reflectance spectrum profile of the double peaks remains almost unaffected by the disturbance of the surrounding temperature but simply shifts. However, once the SRI increases to be larger than the cladding index, the intensity of double peaks decreases dramatically [36].…”
Section: Nonuniform-etched Fbgmentioning
confidence: 99%
“…Recently, optical fiber is widely used in the field of sensors due to its advantages, such as portability, free from electromagnetic interference, low cost, rapid response. Surface plasmon resonance wave optical fiber endecho and fiber grating [1][2][3][4][5] are typical optical fiber sensors to measure refractive index.…”
Section: Introductionmentioning
confidence: 99%
“…Etching method was used to remove the cladding of FBG' grating area and then various sensors based on refractive index were reported [1,2,3,11,12]. In this paper, simultaneous measurement of refractive index and temperature with a side polished fiber Bragg grating (SPFBG) is proposed and demonstrated experimentally to measure refractive index of liquid and temperature simultaneously.…”
Section: Introductionmentioning
confidence: 99%